2020
DOI: 10.1016/j.aninu.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy on growth performance, carcass characteristics, serum biochemical index, and meat quality of female Hu lambs

Abstract: This study evaluated the effects of dietary energy levels on growth performance, carcass traits, meat quality, and serum biochemical of female Hu lambs. Seventy female Hu lambs (aged 4 months) were randomly allotted to 5 dietary treatments. Lambs were fed diets with 5 levels of metabolizable energy (ME): 9.17 (E1), 9.59 (E2), 10.00 (E3), 10.41 (E4), and 10.82 MJ/kg (E5). The lambs were adapted to the experimental diets for 10 d and the experiment period lasted for 60 d. Dry matter intake and feed conversion ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
4
17
0
1
Order By: Relevance
“…The increased plasma albumin concentration can be explained by the rapid production and utilization of albumin for the synthesis of tissue proteins in the chickens consuming HE diets. Our result is in agreement with a previous study by Wang et al (2020), who found that increasing dietary energy was associated with a linear increase in serum albumin in lambs. Albumin has been recognized as one of the essential proteins, majorly known for activities associated with protein synthesis, substrate transport, toxin neutralization, and colloidal osmotic pressure (Levitt and Levitt 2016) during the growth and development process.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The increased plasma albumin concentration can be explained by the rapid production and utilization of albumin for the synthesis of tissue proteins in the chickens consuming HE diets. Our result is in agreement with a previous study by Wang et al (2020), who found that increasing dietary energy was associated with a linear increase in serum albumin in lambs. Albumin has been recognized as one of the essential proteins, majorly known for activities associated with protein synthesis, substrate transport, toxin neutralization, and colloidal osmotic pressure (Levitt and Levitt 2016) during the growth and development process.…”
Section: Discussionsupporting
confidence: 94%
“…A recent study by Wang et al (2020) revealed that dietary FA significantly increased villus height, villus height:crypt depth, and villus surface area in the jejunal mucosa of weaned piglets. Munyaka (2012; 2013) reported that FA modulated immune responses in young laying hens subjected to acute immunological challenge.…”
Section: Introductionmentioning
confidence: 97%
“…The PICRUSt prediction results showed that amino acid metabolism, carbohydrate metabolism, replication and repair, membrane transport, translation, and energy metabolism were the dominant gene families at KEGG level 2, all of which are essential for survival, growth, and reproduction of gastrointestinal microbes (44). These results were similar to our previous studies in sheep (11)(12)(13)(14)(15). Among these gene families, unexpectedly, the genes associated with metabolism of cofactors and vitamins, cellular processes and signaling, metabolism, biosynthesis of other secondary metabolites, infectious diseases, signaling molecules and interaction, nervous system, and digestive system were significantly higher in the PSR silage diet than in the mixed and corn silage diets, while lipid metabolism was dramatically lower in the PSR silage diet than in the corn silage diet.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, the concentration of GLU in the mixed group was significantly lower than in the PSR silage and corn silage treatments, while the higher ADG was observed in the mixed group. These results were inconsistent with previous studies, and this might be related to species and feed composition (11)(12)(13)(14)(15). The concentration of BUN is perceived as an effective indicator to measure the metabolism of protein and amino acid, low BUN level indicates high nitrogen metabolism capacity (21).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation